Evaluation of soil intake by growing Creole young bulls in common grazing systems in humid tropical conditions. (10th January 2017) - Jurjanz, S.; Collas, C.; Lastel, M. L.; Godard, X.; Archimède, H.; Rychen, G.; Mahieu, M.; Feidt, C.
Abstract : Soil is the main matrix which contributes to the transfer of environmental pollutants to animals and consequently into the food chain. In the French West Indies, chlordecone, a very persistent organochlorine pesticide, has been widely used on banana growing areas and this process has resulted in a long-term pollution of the corresponding soils. Domestic outside-reared herbivores are exposed to involuntary soil intake, and tethered grazing commonly used in West Indian systems can potentially favour their exposure to chlordecone. Thus, it appears necessary to quantify to what extent grazing conditions will influence soil intake. This experiment consisted of a cross-over design with two daily herbage allowance (DHA) grazed alternatively. Six young Creole bulls were distributed into two groups (G1 and G2) according to their BW. The animals were individually tethered and grazed on a restrictive (RES) or non-restrictive (NRES) levels of DHA during two successive 10-days periods. Each bull progressed on a new circular area every day. The two contrasting levels of DHA ( P <0.001) were obtained via a different daily grazing surface area (RES: 20 m 2 /animal, NRES: 31 m 2 /animal; P <0.01) offered to the animals by the modulation of the length of the tethering chain (RES: 1.9 m, NRES: 2.6 m). These differences in offered grazing areas resulted in DHA of 71 and 128 g DM/kg BW 0.75, respectively for RES and NRES treatments. As expected, the animals grazing on the reduced area realized a lower daily dry matter intake (DMI) (RES: 1.12 kg/100 kg BW, NRES: 1.83 kg/100 kg BW; P <0.05) and present a lower organic matter digestibility (RES: 0.67, NRES: 0.73; P <0.01) than NRES ones, due in part to the shorter post-grazing sward surface height (RES: 3.3 cm, NRES: 5.2 cm; P <0.01) of their grazing circles. Soil intake was estimated on an individual level based on the ratio of the marker titanium in soil, herbage and faeces. Grazing closer to the ground, animals on RES treatment ingested a significantly higher proportion of soil in their total DMI (RES: 9.3%, NRES: 4.4%; P <0.01). The amount of ingested soil in the diet was not significantly different between the two treatments (RES: 98 g/100 kg BW, NRES: 78 g/100 kg BW; P >0.05) due to the lower DMI of RES compared with NRES treatment.